PSYCHOLOGICAL PROBLEMS IN SPEAKING ENGLISH OF THE STUDENTS OF VOCATIONAL SENIOR HIGH SCHOOL - Anam, Mukhtarul; Tantri, Tantri (E-Link Journal, 2020)
The purpose of the research is to know the studentsâ€™ psychological problems, and to know the efforts of the students to overcome their psychological problems. The research was conducted in SMKN 1 Lamongan at OTKP. The research is qualitative research. It used an observation and a semi-structured interview as a technique to collect the data. Based on the research, the researcher found that the students felt anxious, shy, fear of making mistakes and the students also got a lack of confidence when they were speaking in front of the class. The efforts to overcome their psychological problems were as follows. The students should have the self-confidence to speak, the student should master many vocabularies, and more practices speaking in English, the teacher should give motivation to the students and encourage a habit and accustom the students to use English.Â Keywords: Speaking, psychological problems